Strategi Pemberdayaan Wanita Tani Penyangga Ketahanan Pangan Perkotaan Melalui Program Pekarangan Pangan Lestari - Yusriadi; Suherman; Aldilla, Dilla; Nuddin, Andi (Edupedia Publisher, 2024)
This research focuses on the development strategy of Women Farmer Groups (KWT) through the Sustainable Food Farms (P2L) program in Parepare City. Analysis of internal and external factors shows that the success of KWT is influenced by forces such as government support through P2L, strong KWT institutions, and the availability of companions. Meanwhile, weaknesses include a lack of fulfillment of market demands and internal group conflicts. In facing opportunities and threats, the proposed strategy involves selecting crops with short harvest times, partnerships with farmers and traders, and increasing group awareness of the final results of the P2L program. Applying the SWOT matrix produces main strategies, such as increasing production by focusing on crops of interest, diversifying plantings, and optimizing yard functions. The research concludes that the KWT in Parepare City is in an aggressive condition, showing significant development potential. This development strategy includes strengthening institutions, increasing production, and diversifying crops to optimize the potential of natural and human resources. Education, training, and new technologies are keys to success in overcoming challenges such as price fluctuations and climate change in the urban agricultural sector.